Barter Credit: Warehouses as a Contracting Technology - SKRASTINS, JANIS (Journal of Finance, 2023)
ABSTRACT A large Brazilian agribusiness lender introduces a new contracting technology: grain warehouses. Using runner‐up warehouse locations as a control group, I find that construction of these warehouses permits a new debt contract, namely, barter credit repayable in grain. This contract increases borrowers' debt capacity and reduces borrowing costs. The effects are stronger when grain price risk is higher, for municipalities with weaker courts, and for financially constrained borrowers. These findings are consistent with barter credit reducing financial market imperfections by mitigating borrowers' output price risk.